Contriving a novel multi-epitope subunit vaccine from Plasmodium falciparum vaccine candidates against malaria - Collins Ojonugwa Mamudu,, Franklyn Nonso Iheagwam,, Esther Ogechi Okafor,, Titilope Modupe Dokunmu,, Olubanke Olujoke Ogunlana, (Journal of Applied Pharmaceutical Science, 2024)
In this study, immunoinformatics strategies were used to design a subunit vaccine against malaria from immunogenic regions of three Plasmodium falciparum surface antigens; liver stage antigen 3-C (V750-K1433), merozoite surface antigen 180 truncate-4 (A805-P1093), and merozoite surface protein 10 region 1 (D29-N188). A multi-epitope subunit vaccine construct (VC) was designed from immunodominant B- and T-cell epitopes followed by structure prediction, evaluation, and validation. Toll-like receptors (TLRs) 2 and 4 were docked with the VC. Their complexes’ molecular dynamics, immune stimulation, codon optimization, and in silico cloning of the VC were simulated. The VC is a 49.2 kDa antigenic and nonallergenic protein, comprised of 26% α-helix, 7% β-strand, 66% coil. The immune simulation test showed that the vaccine could provoke adaptive immune responses, and molecular docking tests showed that it interacts strongly with TLR-2 (−945.1 kcal/mol) and TLR-4 (−919.8 kcal/mol) to form complexes of high stability that hardly deform. The guanine-cytosine content and codon adaptation index of the VC were 42.94 and 0.99 after codon optimization. Escherichia coli pET-28a(+) was identified as the best vector for optimal gene expression. In conclusion, the study reveals that the VC shows promising results in neutralizing falciparum malaria.
Keywords: Epitopes, immunoinformatics, malaria, Plasmodium falciparum, vaccine construct